Experimental Study on Physio-Chemical Characteristics of Stinging Nettle Fiber Toward Compatibility for Polymer Composites Used in Wind Turbine Blade Application - Nsanzumuhire C.; O. O. Daramola; I. O. Oladele; A. D. Akinwekomi; F. O. Aramide; Mwasiagi Josphat Igadwa; Ben Dulo; T. Habanabakize (Journal of Natural Fibers, 2025)
This study investigated the compatibility of stinging nettle (urticadioica) fiber to improve the performance characteristics of wind turbine blade applications. The fiber was extracted using the water retting method, and the alkali treatment was performed using 6% NaOH. This concentration was reported to be optimal for the alkaline treatment of many natural fibers. The fiber maximum normal density achieved was 1.213 g/cm3 and 1.229 g/cm3 for raw and alkali-treated samples. Through alkali treatment, the linear density reduced from 12.64 taxes to 11.98 taxes with a decrease of 5.509%, whereas the maximum breaking force increased from 5.51 to 5.82 N, and the breaking elongation increased from 0.63% to 0.71%. It was further observed that the tenacity of the untreated and treated samples was, respectively, 43.67 and 46.12 cN/tex. The maximum cellulose content of 78.736% was achieved with alkali treatment, whereas hemicellulose, lignin, moisture content, extractives, and volatile matter decreased. On the other hand, the ash content, alpha-cellulose, and holocellulose contents increased with alkali treatment. Owing to its properties compared to other natural fibres used for wind turbine blades, the achieved alkali-treated fibre can also be considered a better reinforcement to improve the mechanical characteristics of polymer composites for this area. The novelty of this work is to evaluate the compatibility of stinging nettle fibre as a reinforcement material in polymer composites for wind turbine blade applications, given the global push towards more sustainable and biodegradable alternatives to synthetic fibre-reinforced composites. Keywords: Chemical characterization, natural fibre-reinforced polymer composites, single fibre tensile strength, stinging nettle fibre, wind turbine blade application, wind energy.